Fatal Disseminated Pseudomonas Aeruginosa Infection in a Captive Green Iguana (Iguana iguana) - Šupić Jovana; Rešidbegović Emina; Koro Amira; Hadžiabdić Sead; Golob Majda; Škapur Vedad; Alić Amer (Acta Veterinaria, 2021)
Infections with various bacteria, especially gram-negative aerobes, are a well-recognized problem in captive cold-blooded animals with immunocompromised health status, or in those kept under poor conditions. Pseudomonas is one of the most represented genera. Here, we present a case of fatal disseminated infection caused by Pseudomonas aeruginosa in a captive green iguana kept at the “Pionirska dolina” Zoo in Sarajevo, Bosnia and Herzegovina. At necropsy, severe stomatitis, pneumonia, hepatitis and nephritis, accompanied with focally extensive dermatitis were observed. Histopathology revealed multifocal necrosis in various visceral organs. Culture and subsequent MALDI-TOF MS analysis were conducted to identify the isolate as P. aeruginosa. Antimicrobial susceptibility testing revealed a wide susceptibility of the isolate, however applied therapy was instilled too late in the presented case. This case demonstrates the significance of timely and accurate identification, and antimicrobial susceptibility testing of bacterial isolates implicated in the pathology of captive reptiles. The importance of monitoring the adequate environmental conditions (enclosure temperature, humidity and conformation), health status and possible clinical signs of illness are highlighted.